Hubungan Higiene Perorangan dan Cara Penyemprotan Pestisida dengan Tingkat Keracunan Pestisida pada Petani di Desa Kembang Kuning Kecamatan Cepogo - Qisthi Wahida Rusdita, Aulia, Heru Subaris K, SKM.,M.Kes, Dwi Astuti SKM, M.Kes (2016)
Spraying pesticides that do not meet the rules of the incidence of poisoning resulting impact on farmers to do with the blood cholinesterase activity. Class of organophosphate pesticides can affect nerve function by inhibiting the enzyme kolinesterse. The purpose of this study was to analyze the personal hygiene and spraying associated with toxicity in a farmer spraying pesticide use on vegetables in Kembang Kuning Cepogo District of Boyolali. The study design used is cross sectional study. The population in this study of 40 farmers. Sampling with exhaustive sampling of 40 farmers. Analysis of the relationship is done with statistical analysis Fisher exact test. The results showed blood tests obtained from respondents who poisoned a total of 33 respondents (89.2%). The risk factors that influence pesticide poisoning (<0.05) the variable of personal hygiene and spraying. The results of the bivariate analysis suggested a link between personal hygiene level of pesticide poisoning in farmers in Kembang Kuning Cepogo Boyolali District of 2016 with a value of p = 0.038. As well There is a relationship between how spraying with pesticide poisoning rate on farmers in the village Kembangkuning Cepogo Boyolali District of 2016 with a value of p = 0,026